Pengaruh Opini Audit, Pertumbuhan Perusahaan, Profitabilitas dan Kompleksitas Perusahaan terhadap Auditor Switching - Yanti, Novellia Hendri; Setiawan, Mia Angelina (Jurnal Eksplorasi Akuntansi, 2025)
This research aims to determine the effect of audit opinion, company growth, profitability and the company complexity on auditor switching. The population in this study are financial companies listed on the Indonesia Stock Exchange (IDX) in 2016-2021. The research sample was determined using the purposive sampling method with a total sample of 36 companies. The data used is secondary data from the official website of finance companies. The analytical method used is logistic regression with SPSS. The of this study showed that audit opinion, company growth, profitability and the company complexity doesn’t affect the auditor switching.